Axial length, anterior chamber parameters, and white-to-white corneal diameter: Their inter-correlations with intraocular pressure among young Saudis - Alotaibi, Wafa; Saif Alrasheed (Journal of the Pakistan Medical Association, 2025)
Objectives: To evaluate axial length, anterior chamber angle, anterior chamber depth, refractive errors and white-to-white corneal diameter, and to assess their inter-correlations with intraocular pressure among young individuals. Method: The prospective, cross-sectional study was conducted at the optometry clinics of King Saud University, Riyadh, Saudi Arabia, between January and April 2022, and comprised healthy subjects of either gender aged 8-37 years. Ocular parameters were noted, and the subjects were screened for ocular disorders with a slit lamp. The refractive error was assessed using an auto-refractometer. Data was analysed using SPSS 25. Results: Of the 108 subjects, 61(56.5%) were females and 47(43.5%) were males. The overall mean age was 20.87±6.23 years. The mean anterior chamber angle was 39.26±5.04 degrees, mean anterior chamber depth was 3.06±0.30mm, mean white-to-white corneal diameter was 11.97±0.40mm, and mean intraocular pressure was 18.75±1.68mmHg. Intraocular pressure had a positive but non-significant correlation with myopia, anterior chamber angle, anterior chamber depth and axial length (p>0.05). Conversely, intraocular pressure had inverse but non-significant correlation with age, hyperopia and white-to-white corneal diameter (p>0.05). Conclusion: Ocular biometric dimensions could be considered while assessing the risk factors for ocular hypertension. Key Words: Young adult, Clinical practice, Retina, Risk factors, Intraocular pressure.